If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -1(2x + -8) = 5 + -3x Reorder the terms: 7 + -1(-8 + 2x) = 5 + -3x 7 + (-8 * -1 + 2x * -1) = 5 + -3x 7 + (8 + -2x) = 5 + -3x Combine like terms: 7 + 8 = 15 15 + -2x = 5 + -3x Solving 15 + -2x = 5 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 15 + -2x + 3x = 5 + -3x + 3x Combine like terms: -2x + 3x = 1x 15 + 1x = 5 + -3x + 3x Combine like terms: -3x + 3x = 0 15 + 1x = 5 + 0 15 + 1x = 5 Add '-15' to each side of the equation. 15 + -15 + 1x = 5 + -15 Combine like terms: 15 + -15 = 0 0 + 1x = 5 + -15 1x = 5 + -15 Combine like terms: 5 + -15 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| 2x^2=-2x+5 | | 2x=x/2+10 | | 10x+5x-2x=69 | | 208-3x=x+(x+1)+(x+2)+(x+3)+(x+4)-50 | | 3x+36=10x-48 | | y=25x-7 | | x^4+4x^3+1=0 | | 8(m-1)-7(m+3)=-29 | | 3x+108=9x-12 | | -5x-3(-x+1)=7 | | N+6=-44 | | 107-7x=29x+23 | | 2x/4=6*3 | | 150-5x=22x+18 | | -6x-6(-4x-11)=12 | | 12x^2-40=17x | | (x-7)=(x+3) | | y=-4(-2)-5 | | 23=m-9 | | 7.31=d+3.31 | | 5x+2x=55 | | 2-7x=1-6x | | x^2-15*8= | | x^3-10x^3+21x=0 | | 12x+11=119 | | y=-2-2-3-2-4 | | (6*2-4)/2 | | x-9y=-21 | | 8+3x/5=x | | x^2-11x+30x=0 | | (15*2x)(8*2x)-15*8= | | 3/10(24/130) |